PENGARUH KESADARAN WAJIB PAJAK, PEMAHAMAN PAJAK DAN SANKSI WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Pradnya Wikrama Suputra, I Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024DO - 10.24843/EEB.2024.v13.i10.p10, 2024)
Compliance is an obedient behavior or disciplined attitude towards the rules or orders set with the awareness of each individual. Compliance can occur in various forms as long as a person shows obedient behavior and attitude towards something, for example, such as complying with regulations or requests from others. This study aims to analyze the effect of taxpayer awareness, tax understanding and taxpayer sanctions on taxpayer compliance and to determine the dominant variable on compliance of Badung Regency boarding house hotel taxpayers. The population in this study was 254 samples sourced from active taxpayer data at Bapenda Badung Regency in 2023. The data collection method in this study used a questionnaire. The study used a data analysis method, namely multiple linear regression analysis. The analysis tool in this study uses the SPSS for Windows application. The results found that taxpayer awareness has a negative effect on taxpayer compliance. Another finding is that tax understanding has a positive effect on taxpayer compliance. And taxpayer sanctions have a positive effect on taxpayer compliance.